Integrated genomic, mechanistic, and transcriptomic analysis of new Bacillus thuringiensis strains for enhanced biocontrol of agricultural pests - Vladimirivich, Patyka Nikolai; Wang, Renjun; Patyka, Tetiana; Honchar, Anastasiia (Journal of Plant Protection Research, 2025)
Global agricultural systems face increasing challenges due to climate change and the evolution of pesticide-resistant pest strains. Bacillus thuringiensis (Bt) remains a key bioinsecticide, but new strains with enhanced efficacy are urgently needed. This study aimed to identify and comprehensively characterize a new Bt strain, 87/3, and evaluate its entomocidal and antifeedant properties against the Colorado potato beetle (Leptinotarsa decemlineata) and the large cabbage white butterfly (Pieris brassicae). Strain 87/3 demonstrated exceptional entomocidal action, with up to 98.5% mortality of L. decemlineata, and 87.9% against P. brassicae. Genomic analysis revealed a diverse array of insecticidal genes, including new Cry and Vip types. Receptor binding assays confirmed that purified toxins from strain 87/3 have high-affinity binding to the midgut membranes, with different toxin classes binding to different receptors. Transcriptomic analysis showed significant changes in gene expression in the pests after exposure to strain 87/3. This included early activation of detoxification and immune response genes, followed by later disruptions in genes associated with gut integrity and metabolism. These results confirm the exceptional potential of B. thuringiensis, strain 87/3, as a basis for new-generation bioinsecticides and provide molecular data for developing effective resistance management strategies